Produção musical em contextos "residual/emergente" de redes: móveis coloniais de Acaju - Duarte, Emmanuel Vitor Cleto (2014)
This thesis has as its main objective to evaluate how a banda can achieve sustainability and legitimation within the music market nowadays, without a link with a major company, using "residual forms" from the tradicional companies' model, and "emergent forms" as the digital culture, the network production and a direct contact with their users and consumers. For this analysis, Móveis Coloniais de Acaju, a banda from the cultural scene of Brasilia was selected for a case study and an exemple of this "emergent form", also and and exemple of the "residual" strategies used by the artists, within the perspective of cultural producers, production of "materialities", inside a network culture, supported by the theory of Raymond Wlliams, Jesús Martin-Barbero, and Manuel Castells. With more than a decade as musicians in Brazil, the band gathers many characteristics and is able to answer for a production, comercialization and distribution model that operates away from the major record companies and is able do sustain themselves with significant independence. This way, the trajectory of the band and its main strategies for music production were analysed to understand which are the possibilities for artists that operate outside of the circuit of major record companies. Also within the authors that give theoretical and conceptual foundations we can highlight: Herschmann, Janotti. Jr, Freire Filho, within the evaluation of production and the musical market; Jenkins, Lévy e Castells with the reflection about internet culture, interations, participation and convergency as the focus for production in the Internet; Recuero, Fragoso, e Amaral colaborate ith the metodology/field research and with the evaluation of the production within social networks and blogs. The methodology assumes non excludend perspective or multiple relations such as online and offline; "dominant, residual and emergent"; mainstream (major record companies) and independent artists; production, circulationo, apropriation and use of cultural products. The field research was structured with interviews, musicam market data, traditional press articles and the collection of the band's production from the official site, blog and social networks withing twenty months. The first chapter of the thesis does a music market balance and its main changes to evaluate the context where the band is inserted and makes a paralel within the "dominant form"of the major companies and what appears as an "emergent form" of independent bands that work as networks. Te music industry was on of the first ones heavily impacted for the Internet creation and development. Production and consumption were rapidly impacted. The following section evaluates the band since its formation, their relation with the city of Brasilia and its musical and cultural scene, their roots in the University and the way they articulate with the other musicians as a network to answer for the context they appeared and how they develop in the music market. For the third chapter, the way that Móveis Coloniais de Acaju produce in the Intenet in a collective way and interacting with the fans will be evaluated to understand the strategies for creating, distributing and promoting their musical products. Site, blog and social networks (Youtube, Facebook and Twitter) were evaluated to gather exemples of which mechanisms of this "emergent form" are used by the band